A Decomposition Theorem for Positive Maps, and the Projection Onto a Spin Factor - Størmer, Erling (MATHEMATICA SCANDINAVICA, 2016)
It is shown that each positive map between matrix algebras is the sum of a maximal decomposable map and an atomic map which is both optimal and co-optimal. The result is studied in detail for the projection onto a spin factor.